2016
DOI: 10.1007/s13197-016-2192-1
|View full text |Cite
|
Sign up to set email alerts
|

Volatile composition of Pedro Ximénez and Muscat sweet Sherry wines from sun and chamber dried grapes: a feasible alternative to the traditional sun-drying

Abstract: Sweet Sherry wines from Pedro Ximénez and Muscat sun and chamber-dried grapes during vintages 2009 and 2010 were aged in American oak wood for 12 months. Their volatile content was periodically analyzed using SBSE-GC-MS. Cluster analysis and principal component analysis demonstrated that the volatile compounds considered can be used to detect grape variety and vintage. Principal component analysis for each grape variety, clearly differentiated aging time and vintage. Drying type was the least significant facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
4
14
0
Order By: Relevance
“…It can be observed that wood‐derived compounds such as eugenol, trans‐ whiskeylactone, benzaldehyde or 5‐methyl‐2‐furaldehyde, amongst others, significantly increased their concentration during their ageing process. Similar results were obtained in other studies when PX was aged in American oak wood . Other compounds that are not typically released by wood, such as isobutyl acetate or isobutanol, also increased their concentrations during the ageing process.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…It can be observed that wood‐derived compounds such as eugenol, trans‐ whiskeylactone, benzaldehyde or 5‐methyl‐2‐furaldehyde, amongst others, significantly increased their concentration during their ageing process. Similar results were obtained in other studies when PX was aged in American oak wood . Other compounds that are not typically released by wood, such as isobutyl acetate or isobutanol, also increased their concentrations during the ageing process.…”
Section: Resultssupporting
confidence: 89%
“…Similar results were obtained in other studies when PX was aged in American oak wood. [17][18][19] Other compounds that are not typically released by wood, such as isobutyl acetate or isobutanol, also increased their concentrations during the ageing process. This could be explained by concentration processes due to the evaporation of water through wood pores.…”
Section: Validation Of the Sbse Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…This clear differentiation regarding ageing time corresponded to the discrimination observed for the same samples regarding the volatile composition [26]. Thus, the results obtained by means of When the wines are represented on this same plane, it can be seen that those wines, which were aged without any contact with oak (S) presented the lowest values for PC2, that is to say, they exhibited high intensity levels of citric notes, a typical character of Muscat wines when kept under these ageing conditions.…”
Section: Selecting the Ageing Methods For Sweet Wines Made From Grapessupporting
confidence: 67%
“…Research studies on Pedro Ximénez and Muscat sweet musts and wines made from grapes dried both under sunlight and within climate chambers with forced ventilation can be found in the literature [21][22][23][24][25][26], however, no studies have been found to comprise the subsequent optimization of the whole process, namely, fermentation conditions, ageing method and evolution of the product under wood contact.…”
Section: Introductionmentioning
confidence: 99%